[2+2] Cycloaddition of 1,3-Dienes by Visible Light Photocatalysis () - Hurtley, Anna E. (2014)
[2+2] Photocycloadditions of 1,3-dienes represent a powerful yet synthetically underutilized class of reactions. We report that visible light-absorbing transition metal complexes enable the [2+2] cycloaddition of a diverse range of 1,3-dienes. The ability to use long-wavelength visible light is attractive because these reaction conditions tolerate the presence of sensitive functional groups that might be readily decomposed by the high-energy UVC radiation required for direct photoexcitation of 1,3-dienes. The resulting vinylcyclobutane products are poised for a variety of further diversification reactions, and we expect this method to be powerfully enabling in the synthesis of complex organic targets.